CORPORATE GOVERNANCE, DISCLOSURE QUALITY, AND COST OF EQUITY: EVIDENCE FROM PAKISTAN - Amanullah Amanullah; Xinjun Lyu (Universitas Kristen Indonesia Toraja, 2022)
To be successful in the financial world, you must know how the public disclosure of business information affects stock prices. Specifically for Pakistan, this research will help us better understand the relationship between corporate governance, disclosure quality, and equity cost The Sys-GMM model has been employed by 167 non-financial enterprises listed on the Pakistan Stock Exchange since 2017. (PSX). Research shows it was in use between 2018 and 2020. The Sys-GMM technique for estimating may be used to account for endogeneity in corporate governance problems. We discovered that GMM projections failed to account for endogeneity, resulting in inaccurate conclusions, using pooled OLS and fixed-effect estimates. According to the research, the cost of equality and financial transparency are mutually incompatible. All of these factors contribute to the PSE's stock price decline, including board size, concentrated ownership, and CEO duality. The research es-tablishes a relationship between independent audit committees and high-quality audits and reduced equity expenses. Independent directors and competent auditors command a premium on the PSX. The duration of the approval process for financial statements has no bearing on the board's independence. Due to the scarcity of information disclosed in annual reports, investors anticipate a higher rate of return. The conclu-sions of the research may be beneficial to Pakistan's corporate govern-ance authorities and investors.